Principles of macroeconomics. - Mankiw, N. Gregory, 1958- ([S.l.] : Cengage, 2008)
With its clear and engaging writing style, PRINCIPLES OF MACROECONOMICS, 5E, continues to be one of the most popular books on economics available today. Mankiw emphasizes material that you're likely to find interesting about the economy (particularly if you're studying economics for the first time), including real-life scenarios, useful facts, and the many ways economic concepts play a role in the decisions you make every day.
Keywords: macro-economie.